Three Mini-ethnographic Case Studies on COVID: Impacts on Greek Agricultural Sectors - Kim E. Dooley; Evangelos Vergos; Kyriaki Zinoviadou; Konstantinos Rotsios (Journal of International Agricultural and Extension Education, 2022)
COVID was politically polarizing, had global and public health impacts, and created havoc in supply chains. Social dilemmas caused by the pandemic were difficult, but also created opportunities to be resilient and innovative in agricultural extension education. This mini-ethnographic case study examined three Greek agricultural sectors from the perspectives of experts in extension and higher education. Data included semi-structured interviews, review of technical reports, and photographs in developing each case study. From the cross-case analysis, there were four emerging themes: environmental, economic, and social impacts and the innovative solutions used to address these concerns. What we have learned, and where we go from here requires reimagining training and education to broaden our reach and approaches. There is a need to educate stakeholders to access reliable data, become citizen scientists, engage in learning communities in virtual settings across sectors, and become more entrepreneurial to sustain the environment, food security, and financial stability within communities worldwide.
Keywords: Agricultural Sectors; Extension; Food Science; Agricultural Economics; Case Study